2020
DOI: 10.1038/s41467-020-15109-y
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 suppresses ferroptosis through preserving the activity of S-adenosyl homocysteine hydrolase

Abstract: Ferroptosis is a newly characterized form of regulated cell death mediated by iron-dependent accumulation of lipid reactive oxygen species and holds great potential for cancer therapy. However, the molecular mechanisms underlying ferroptosis remain largely elusive. In this study, we define an integrative role of DJ-1 in ferroptosis. Inhibition of DJ-1 potently enhances the sensitivity of tumor cells to ferroptosis inducers both in vitro and in vivo. Metabolic analysis and metabolite rescue assay reveal that DJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 53 publications
3
120
0
2
Order By: Relevance
“…Besides, the suppression was more obvious in DJ-1 ΔC3 and L187E mutants than V51C mutant, indicating that the hydrophobic C terminus may have other effects such as involving regulation of signaling pathway [4, 6, 38]. All these data supported our previous discovery that DJ-1 was a negative modulator of ferroptosis providing new opportunities to facilitate ferroptosis-based cancer therapy [14].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Besides, the suppression was more obvious in DJ-1 ΔC3 and L187E mutants than V51C mutant, indicating that the hydrophobic C terminus may have other effects such as involving regulation of signaling pathway [4, 6, 38]. All these data supported our previous discovery that DJ-1 was a negative modulator of ferroptosis providing new opportunities to facilitate ferroptosis-based cancer therapy [14].…”
Section: Discussionsupporting
confidence: 80%
“…Given that recent study has suggested that DJ-1 could suppress ferroptosis triggered by lipid ROS, the impact of DJ-1 C terminus on the suppression of ferroptosis was next investigated [14]. We utilized Erastin, a classic ferroptosis inducer, to build the model of ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because cysteine is a limiting component of GSH, cysteine levels control ferroptosis. It is thus likely that silencing CAT contributes to maintain cysteine available for ferroptosis inhibition [ 48 ]. Accordingly, Zhang et al showed that suppression of miRNA-9 increased the sensitivity of melanoma cells to ferroptosis-inducing drugs [ 46 ].…”
Section: Cysteine Aminotransferase Structure and Localizationmentioning
confidence: 99%